Current issues of pediatric inflammatory bowel disease in Korea - Oh, Seak Hee; Kim, Kyung Mo (Clinical and experimental pediatrics, 2014)
Inflammatory bowel disease (IBD) is a chronic relapsing disorder of unknown etiology, which is believed to be multifactorial. Recently, the incidence of pediatric IBD has steeply increased in Korea since 2000. Poorly controlled disease activity can result in complications such as intestinal fistulae, abscess, and stricture, as well as growth retardation and delayed puberty in children. Because of a lack of confirmative tests, various diagnostic modalities must be used to diagnose IBD. Onset age, location, behavior, and activity are important in selecting treatments. Monogenic IBD must be excluded among infantile and refractory very-early-onset IBD. Early aggressive therapy using biologics has recently been proposed for peripubertal children to prevent growth failure and malnutrition.